2015
DOI: 10.3390/ijms16034600
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide and Reactive Oxygen Species in the Pathogenesis of Preeclampsia

Abstract: Preeclampsia (PE) is characterized by disturbed extravillous trophoblast migration toward uterine spiral arteries leading to increased uteroplacental vascular resistance and by vascular dysfunction resulting in reduced systemic vasodilatory properties. Its pathogenesis is mediated by an altered bioavailability of nitric oxide (NO) and tissue damage caused by increased levels of reactive oxygen species (ROS). Furthermore, superoxide (O2−) rapidly inactivates NO and forms peroxynitrite (ONOO−). It is known that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
133
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(143 citation statements)
references
References 96 publications
3
133
0
7
Order By: Relevance
“…Placental oxidative stress has been shown to be increased in preeclamptic women, and placental and renal oxidative stress is observed in preclinical models preeclampsia, and it is implicated in contributing to the development of vascular dysfunction, proteinuria, and hypertension during pregnancy (9,13,27,28). Importantly reactive oxygen species (ROS) is a byproduct of inflammation and is elevated in response to RUPP CD4ϩ T cells and IL-17-and AT 1 -AA-induced hypertension during pregnancy.…”
Section: Np T Reg Cell Supplementation Normalizes Tgf-␤ In Rupp Ratsmentioning
confidence: 99%
“…Placental oxidative stress has been shown to be increased in preeclamptic women, and placental and renal oxidative stress is observed in preclinical models preeclampsia, and it is implicated in contributing to the development of vascular dysfunction, proteinuria, and hypertension during pregnancy (9,13,27,28). Importantly reactive oxygen species (ROS) is a byproduct of inflammation and is elevated in response to RUPP CD4ϩ T cells and IL-17-and AT 1 -AA-induced hypertension during pregnancy.…”
Section: Np T Reg Cell Supplementation Normalizes Tgf-␤ In Rupp Ratsmentioning
confidence: 99%
“…1 It is considered as a disease of the maternal endothelium, 2 and the proper function of any endothelium includes maintenance of a barrier and regulation of vascular tone. In preeclampsia, vasoactive substances, such as sFlt-1, are released into the maternal circulation, 3 resulting in reduced nitric oxide (NO) bioavailability, 4 vasoconstriction of the microvasculature, increased peripheral resistance, and hypertension. 5 Several attempts have been described to quantify the degree of peripheral vascular resistance, endothelial dysfunction (EDF), and microvascular constriction indirectly; however, a direct method of visualizing and measuring microvascular changes during pregnancy may advance understanding of the development of preeclampsia and support clinical risk stratification in pregnancy.…”
mentioning
confidence: 99%
“…However, there is controversy about the same levels in relation to the PEC, because some studies report increased expression of iNOS, still others have found the opposite [11,12,13].…”
Section: Resultsmentioning
confidence: 99%
“…Finding increased expression of iNOS and eNOS in placenta of women with PEC [11]. Perhaps related to alterations in the bioavailability of nitric oxide, being the inflammatory process induces iNOS [12].…”
Section: Introductionmentioning
confidence: 99%